Metacognitive training “Through the Glass”: performing arts education in high-dropout apulian schools - Gianeselli, Irene; Bosco, Andrea (Form@re - Open Journal per la formazione in rete, 2025)
The study presents the results of the Metacognitive Training “Through the Glass” (MTTG), which incorporates Performing Arts Education (PAE) enhancing motivation and self-assessment among students. The participants, from technical schools and vocational institutes with high-dropout rates in Puglia, were divided into randomized workshops groups. The quantitative data analysis focused on variables measured through the pre- and post-intervention questionnaire. The observed variables were awareness of metacognitive process and students’ interpretation of the construct self-assessment related to PAE. The MTTG is based on Student Voice and combines a democratic teaching, inspired by Pier Paolo Pasolini’s 1968 “Manifesto per un nuovo teatro”. Training metacognitivo “Attraverso lo Specchio”: performing arts education in scuole pugliesi con alto tasso di dropout. Lo studio presenta gli esiti del training metacognitivo “Attraverso lo Specchio” (TMAS), che utilizza le arti performative per migliorare motivazione e autovalutazione negli studenti. I partecipanti, provenienti da scuole tecniche e istituti professionali pugliesi con alto tasso di abbandono scolastico, sono stati suddivisi in gruppi laboratoriali randomizzati. L’analisi quantitativa si concentra sulle variabili identificate mediante un questionario somministrato pre- e post-intervento. Le variabili osservate misurano la consapevolezza degli studenti sulla metacognizione e la loro interpretazione del costrutto autovalutazione in relazione alla Performing Arts Education. Il TMAS, basato su Student Voice, combina una didattica democratica, ispirata dal “Manifesto per un nuovo teatro” di Pier Paolo Pasolini del 1968.